Impactos de la eliminación de los residuos sólidos urbanos en la salud pública y medio ambiente del sector rondón- Chachapoyas - Carranza Serrano, Jose Luis (2019)
ABSTRACT Environmental and health impacts were evaluated, caused by the inadequate disposal of urban solid waste in the "El Atajo" stream of the Rondón sector, based on the determination of physical parameters (T °, pH, dissolved oxygen and conductivity), chemical (DQO, DBO5, SST and hardness) microbiological (total and thermotolerant coliforms), heavy metal analysis (Hg, Pb, Cd) and through the use of the matrix according to Conesa. The results obtained were compared with the national environmental quality standards for water category 4. Sampling took place during the growing and low water seasons, establishing five sampling stations at strategic places on the path of the stream (E1; E2; E3) and in the Sonche river (E4; E5); Some of the samples were analyzed in the soil and water research laboratory of the national university Toribio Rodríguez de Mendoza -Amazonas for their respective analyzes. The results of the analysis of the physical parameters in the growing period were within the ranges established by the ECA -water, while in the dry season in the E2 (4.75 mg /l); and E3 (3.75 mg /l) the level of dissolved oxygen was found below the ECA. For the chemical parameters in the growing period the DBO5 values were found below the ECA; the result of the analysis of SST in the E2 (130 mg /l) exceeded that established in the standards; likewise in the E1 (96 mg /l) a value close to what was allowed was obtained. In the dry season, all values were below the ECA on the other hand, heavy metal analyzes were high with respect to the ECA. It was found that the health effects were respiratory diseases with 38 %. According to the Conesa matrix an impact qualified as severe was obtained.